Imagining township economies: an urban design approach to unlocking socio-economic transformation_the case of Mamelodi Township - Koma, Olga (My University, 2020)
South Africa’s urban landscape has been systematically structured since the dawn of colonialism with apartheid reinforcing policies that inherently rendered township spaces as mere dormitories for the use and/or disposal thereafter of black people. One cannot speak of an urban context devoid of the rural areas, especially the apartheid created ‘Bantustans’ homelands. While on the one hand Bantustans (which were structured along ethnic lines) were created as administrative rural areas for blacks, they were ultimately down trodden barren areas which housed the old, senile and those too young to enter the economic system. The conditions of Bantustans were such that eventually one was forced to leave the area to seek economic opportunities in white areas. As such townships were created as areas that would temporarily house the black labour force, i.e. those that were seeking employment in urban (white) areas and those already employed. Urban (white) areas were fully functional areas which were developed and fully integrated into the wider global economy. These areas functioned the same way as other urban areas, except for the fact that they were devoid of black people who were treated as immigrant labourers. While cities worldwide have a clear symbiotic distinction between rural and urban areas, South African cities are classified between bantustans, white farms, townships and functional urban areas. The spatial pattern of which is a deliberate restructuring of spaces engineered across racial lines for the purposes of providing cheap and temporary labour (townships), and areas were once that labour has reach its lifespan it can be disposed of (Bantustans). The spatial pattern in urban areas was such that townships were on the outskirts of urban areas (a radius from 10km to 60km outside the city- not too far and not too close). In an effort to reinforce segregation, townships were created in such a way that they have industrial and/or natural buffers. The main mode of transit between the township and the white areas was rail. The spatial design of the township had one road entrance and exit, housing was temporarily designed following temporal theories of housing. The houses represented “highly controlled bedroom communities” (Findley et al, 2011: no page number). Furthermore, the areas were designed as sterile spaces deprived of services and spaces not conducive to the development of a human’s psyche (See figure of Mamelodi Plan). There were no cultural or social spaces. In spite of this, informality (transport, economy, housing, arts and culture) soon thrived, and they became spaces of responsive urbanism. These areas came to symbolize survival, creativity, struggle, and meaning. Many political, cultural leaders were born in townships. Even today, these areas still hold sentimentality for many people even though they remain on the outskirts of functional urban areas. During apartheid economic activity in townships was not only limited but also restricted in terms of the activities that could take place there. Furthermore, townships were designed as spaces where only consumption could occur, and thus rendered the economic activity there economically unproductive. To a large extent townships are still viewed as spaces which are synonymous with informality, and to a large extent that holds true still. Townships however have also evolved as with the turn into democracy. They have grown, some have formalized and governance has been restructured. Transformation programmes that have been undertaken in townships, most specifically in Mamelodi have been undertaken with little co-ordination and integration between private and public actors. This lack of coordinated effort often results in very low socio-economic impact. In 2014, the Gauteng Department of Economic Development developed a strategy called “Gauteng Township Economy Revitalisation Strategy 2014-2019” the aim of which was to initiate conversation around ways in which existing township economies can be‘ modernized’, ‘formalized’ and‘ re- industrialized’ (Gauteng Department of Economic Development, 2014). The strategy was a response to national government’s calls for unemployment and poverty alleviation. Gauteng’s strategy was specifically a response to the National Development Plan (NDP), which called for job creation. The research report is thus premised on this strategy document, to visualize a transformed township
A research report submitted in partial fulfilment for the degree of Master of Urban Design for the Faculty of Engineering and the Built Environment, University of the Witwatersrand, 2020